Chelating Polymers for Hereditary Hemochromatosis Treatment - Groborz, Ondřej; Poláková, Lenka; Kolouchová, Kristýna; Švec, Pavel; Loukotová, Lenka; Miriyala, Vijay Madhav; Francová, Pavla; Kučka, Jan; Krijt, Jan; Páral, Petr; Báječný, Martin; Heizer, Tomáš; et al. (Macromolecular bioscience, 2020)
Hemochromatosis (iron overload) encompasses a group of diseases that are characterized by a toxic hyperaccumulation of iron in parenchymal organs. Currently, only few treatments for this disease have been approved; however, all these treatments possess severe side effects. In this study, a paradigm for hemochromatosis maintenance/preventive therapy is investigated: polymers with negligible systemic biological availability form stable complexes with iron ions in the gastrointestinal tract, which reduces the biological availability of iron. Macroporous polymer beads are synthesized with three different iron-chelating moieties (benzene-1,2-diol, benzene-1,2,3-triol, and 1,10-phenanthroline). The polymers rapidly chelate iron ions from aqueous solutions in vitro in the course of minutes, and are noncytotoxic and nonprooxidant. Moreover, the in vivo biodistribution and pharmacokinetics show a negligible uptake from the gastrointestinal tract (using 125 I-labeled polymer and single photon emission computed tomography/computed tomography), which generally prevents them from having systemic side effects. The therapeutic efficacy of the prepared polymers is successfully tested in vivo, and exhibits a significant inhibition of iron uptake from the gastrointestinal tract without any noticeable signs of toxicity. Furthermore, an in silico method is developed for the prediction of chelator selectivity. Therefore, this paradigm can be applied to the next-generation maintenance/preventive treatment for hemochromatosis and/or other diseases of similar pathophysiology.
Keywords: benzen; teoretické modely; železo; tomografie emisní počítačová; hemochromatóza; Polymers; lidé; gastrointestinální trakt; Iron Chelating Agents; Benzene; Phenanthrolines; Tomography, Emission-Computed; Iron; polymery; fenantroliny; Gastrointestinal Tract; Hemochromatosis; Models, Theoretical; chelátory železa; Humans